2014
DOI: 10.13005/bbra/1265
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Protection in Dental Radiology-The Safe Use of Radiographs in Dental Practice

Abstract: Radiographs have been widely used in dentistry for various reasons such as diagnosis, treatment planning, during the treatment procedures and assessment of treatment outcome. In our routine dental practice dentists practice intraoral radiography in their clinics. The radiograph when made immediately in the dental chair is a real-time diagnostic aid but the dentist should also confirm whether he/she follows all the guidelines and safety precautions of radiation safety while exposing the patient to X-rays so tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…(Sudarsini et al, 2020) Protective equipments are used to shield the sensitive and compromised patients from unnecessary radiation exposure. (American Academy of Pediatric Dentistry, 2018; American Dental Association, 2012; Crane & Abbott, 2016;FDI World Dental Federation, 2014;Firetto et al, 2019;Kühnisch et al, 2020;Nisha et al, 2014;Radan, 2017). A study found that children are more likely than adults to get cancer following radiation exposure because their tissues and organs are still in the development stage.…”
Section: Worldwide Review Of Dental Radiation Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…(Sudarsini et al, 2020) Protective equipments are used to shield the sensitive and compromised patients from unnecessary radiation exposure. (American Academy of Pediatric Dentistry, 2018; American Dental Association, 2012; Crane & Abbott, 2016;FDI World Dental Federation, 2014;Firetto et al, 2019;Kühnisch et al, 2020;Nisha et al, 2014;Radan, 2017). A study found that children are more likely than adults to get cancer following radiation exposure because their tissues and organs are still in the development stage.…”
Section: Worldwide Review Of Dental Radiation Safetymentioning
confidence: 99%
“…(Kutanzi et al, 2016) Protective measures, such as standing behind protective barrier and increasing the distance between operators and the x-ray machine, are also required to protect operators from unnecessary radiation exposure. (American Dental Association, 2012;FDI World Dental Federation, 2014;Nisha et al, 2014) In a research study, the positioning of handhelds x-ray devices has an impact on radiation received by operators, therefore it is important to use anti-scatter grid to provide a safe zone. (Makdissi et al, 2016) According to other studies, there is correlation between dental x-ray exposure to cancers and tumors in the head and neck regions of dental practitioners and radiographers.…”
Section: Worldwide Review Of Dental Radiation Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Xray radiations are ionizing radiations, thus it is necessary for the radiation exposure prevention protocols to be followed strictly. The ALARA principle is a guideline stating that the radiation exposure should be As Low As Reasonably Achievable (Nisha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%